2015
DOI: 10.1111/weng.12161
|View full text |Cite
|
Sign up to set email alerts
|

English in television commercials in Belgium, France, Italy, the Netherlands and Spain

Abstract: This study investigates and compares the use of English in 1,539 prime time television commercials from five European countries: Belgium, France, Italy, Spain and the Netherlands. Our study contributes to the existing body of research by adding two methodological issues. First, we investigate whether results differ depending on which definition of the term 'English word' is used (i.e. a strict or a broad definition). Second, we explore which factor best predicts the occurrence and the amount of English used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The majority of films and TV series are broadcast in their original English-language version with subtitles (Edwards 2016, 48-51). In advertising, English words and phrases are commonly used both in print media and in commercials on radio and television, while all-English advertisements are also used but less frequently (Gerritsen et al 2000;Gerritsen et al 2007;Raedts et al 2015).…”
mentioning
confidence: 99%
“…The majority of films and TV series are broadcast in their original English-language version with subtitles (Edwards 2016, 48-51). In advertising, English words and phrases are commonly used both in print media and in commercials on radio and television, while all-English advertisements are also used but less frequently (Gerritsen et al 2000;Gerritsen et al 2007;Raedts et al 2015).…”
mentioning
confidence: 99%
“…A number of studies have shown how English is largely present in advertising discourse across contexts that are officially bilingual (Bhatia, , , ; Bhatia & Bhargava, ; Bhatia & Ritchie, ; India, Kathpalia & Ong, ). Mixing with English has also been substantially documented in territories belonging to what Kachru defined as the Expanding Circle, with studies set in Europe (Cheshire & Moser, ; Dimova, ; Gerritsen, Korzilius, van Meurs, & Gijsbers, ; Martin, , , , ; Pétery, ; Piller, , ; Planken, van Meurs, & Radlinska, ; Raedts, Dupré, Hendriclx, & Debrauwere, ; Ustinova, , ; Ustinova & Bhatia, ; Vettorel, ) and elsewhere (Alm, ; Baumgardner, ; Friedrich, ; Martinez, for South America; Baumgardner & Brown, for Iran; Lee, for Korea; Leung, for Hong Kong; Hsu, and Chen, for Taiwan). In these contexts, despite having no official role, English is largely taught as the main foreign language, and it is increasingly present in the media and in the linguistic landscape, as well as used as an international lingua franca of communication.…”
Section: English and Other Languages In Advertisingmentioning
confidence: 99%
“…Studies of this nature have spanned the globe, focusing on different countries in Africa, Asia, Europe, and the Americas (Akinyi, ; Alm, ; Baumgardner, , ; Baumgardner & Brown, ; Cheshire & Moser, ; Friedrich, ; Gerritsen et al., ; Hsu, ; Kamwangamalu, ; Martin, ; Martinez, ; Masavisut, Sukwiwat, & Wongmontha, ; Meraj, ; Mutonya, ; Pétery, ; Rosendal, ; Ruellot, ; Shooshtari & Allahbakhsh, ; Takashi, ; Ustinova, , ; Vaičenonienė, ; Vettorel, ). Although the bulk of this research pertains to print advertisements, this phenomenon has also been investigated in other media, including television (Dimova, ; Lee, ; Martin, ; Raedts, Dupré, Hendrickx, & Debrauwere, ; Tajolosa, ; Ustinova & Bhatia, ; Zhang, ), radio (Pavlou, ), and Internet advertising (Lee, , ; Martin, ). Researchers have also been examining consumers’ attitudes towards various code‐mixed patterns in advertising and, subsequently, the impact of language mixing on advertising effectiveness (Ahn, La Ferle, & Lee, ; Hsu, , , ; Koslow, Shamdasani, & Touchstone, ; Luna & Peracchio, ).…”
Section: The Discourse Of Advertisingmentioning
confidence: 99%